Mapping nonrecombining regions in barley using multicolor FISH - Karafiátová, M; Bartoš, J; Kopecký, D; Ma, L; Sato, K; Houben, A; Stein, N; Doležel, J (Chromosome research, 2013)
Fluorescence in situ hybridization (FISH) is a widely used method to localize DNA sequences on chromosomes. Out of the many uses, FISH facilitates construction of physical maps by ordering contigs of large-insert DNA clones, typically bacterial artificial chromosome (BAC) and establishing their orientation. This is important in genomic regions with low recombination frequency where genetic maps suffer from poor resolution. While BAC clones can be mapped directly by FISH in plants with small genomes, excess of repetitive DNA hampers this application in species with large genomes. Mapping single-copy sequences such as complementary DNA (cDNA) is an attractive alternative. Unfortunately, localization of single-copy sequences shorter than 10 kb remains a challenging task in plants. Here, we present a highly efficient FISH technique that enables unambiguous localization of single copy genes. We demonstrated its utility by mapping 13 out of 15 full-length cDNAs of variable length (2,127-3,400 bp), which were genetically defined to centromeric and pericentromeric regions of barley chromosome 7H. We showed that a region of 1.2 cM (0.7 %) on genetic map represented more than 40 % of the physical length of the chromosome. Surprisingly, all cDNA probes occasionally revealed hybridization signals on other chromosomes, indicating the presence of partially homologous sequences. We confirmed the order of 10 cDNA clones and suggested a different position for three cDNAs as compared to published genetic order. These results underline the need for alternative approaches such as FISH, which can resolve the order of markers in genomic regions where genetic mapping fails.
Keywords: DNA, Plant; Hordeum; Chromosomes, Plant; Sequence Analysis, DNA; In Situ Hybridization, Fluorescence; klonování DNA; genetické markery; Contig Mapping; kontigové mapování; Genome, Plant; sekvenční analýza DNA; hybridizace in situ fluorescenční; Genetic Markers; DNA rostlinná; Nucleic Acid Hybridization; ječmen (rod); Chromosomes, Artificial, Bacterial; hybridizace nukleových kyselin; chromozomy rostlin; Cloning, Molecular; genom rostlinný; umělé bakteriální chromozomy